Effect Of Al Addition To Imc Formation, Mechanical And Wetting Properties Of Low-Ag Sac Solder Alloy - Kamarudin, Maslina (2015)
The effect of various percentages of Al addition to the microstructure of bulk, intermetallic compound (IMC) formation, wetting properties and mechanical properties of Sn-0.3Ag-0.5Cu (SAC0305) solder alloy was investigated. SAC0305, SAC-0.5Al, SAC-1Al, SAC-1.5Al and SAC-2Al were prepared via casting process. The solder alloys were reflowed onto Cu substrate at 260 ºC for 10 seconds. The composition of each solder alloys were determined using XRF. DSC was used to evaluate the thermal characteristics while wetting balance test and spreading test were used to analyze the wettability. The microstructures of the bulk solder as well as the interfacial IMC layer were observed using SEM equipped with EDX. Meanwhile, ball shear test was carried out to assess the reliability of the solder joints. The wettability of solder alloys decreased with the increasing amount of Al, but still within the acceptable range. Addition of Al resulted in the formation of Ag3Al and Cu-Al IMC, lowered the amount of Ag3Sn and Cu6Sn5 IMC and refined β-Sn dendrites. Further addition of Al above 1 wt.% resulted in the formation of primary Al particles. The amount of Ag3Al and Cu-Al IMC and primary Al particles increased with increasing amount of Al. The Al-added solder alloys gave thinner IMC layer (0.62 μm to 1.15 μm) at the solder joint compared to SAC0305 (2.39 μm) for as reflowed conditions and also after isothermal aging. The shear strength of Al added solder alloys which ranging from 21.93 MPa to 19.96 MPa were higher than SAC0305 (19.21 MPa) but lower than SAC305 (35 MPa). SAC-1Al was found to be the xxiii best solder alloy compared to the other four due to its fine microstructure, thin IMC layer, acceptable wetting and high shear strength.